2020
DOI: 10.21203/rs.3.rs-60579/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monocyte-driven atypical cytokine storm and aberrant neutrophil activation as key mediators of COVID-19 disease severity

Abstract: Epidemiological and clinical reports have indicated that the host immune response to SARS-CoV-2, more so than viral factors, determines COVID-19 disease severity. To elucidate the immunopathology underlying COVID-19 severity, cytokine and multiplex immune profiling was performed in mild-moderate and critically-ill COVID-19 patients. Hypercytokinemia in COVID-19 differed from the IFN-γ-driven cytokine storm in macrophage activation syndrome, and was more pronounced in critical versus mild-moderate COVID-19. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
6
7
0
Order By: Relevance
“…Likewise, Severe patients presented an elevated level of blood IL6 ( Figure S2A ). These results are consistent with the previously reported production of pro-inflammatory cytokines by monocytic cells in patients with severe disease (Hadjadj et al, 2020; Vanderbeke et al, 2021) , and provided further insights into the differential responses of other cells.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, Severe patients presented an elevated level of blood IL6 ( Figure S2A ). These results are consistent with the previously reported production of pro-inflammatory cytokines by monocytic cells in patients with severe disease (Hadjadj et al, 2020; Vanderbeke et al, 2021) , and provided further insights into the differential responses of other cells.…”
Section: Resultssupporting
confidence: 92%
“…Overall, the patients experiencing mild infection demonstrated high IFN-I/λ blood levels at early time-points. Furthermore, the inflammatory response appeared to be correlated with disease severity, in agreement with previous reports (Galani et al, 2021; Hadjadj et al, 2020; McGonagle et al, 2020; Vanderbeke et al, 2021) .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are in line with the previously reported enhanced myeloperoxidase (MPO) levels in COVID-19 plasma. 25 A trend towards enhanced neutrophil , (e) CXCL8, (f) CXCL10 and (g) CXCL11 in plasma samples from COVID-19 patients who stayed at the ICU [samples were collected during the first 48 h after admission (ICUday 1; n ≥ 10), after one week (ICUday 7; n ≥ 10) and upon discharge from the ICU (ICUdischarge; n ≥ 10)], COVID-19 patients who were hospitalised in general wards (ward; n ≥ 13) and healthy controls (HC; n ≥ 7). Moreover, (h) CD26/DPP4 enzyme activity was determined in a substrate conversion assay.…”
Section: Altered Levels Of Circulating Proteases Indicate Neutrophil Hyperactivation In Patients With Severe Covid-19mentioning
confidence: 99%
“…In addition, analysis of a single-cell RNAsequencing dataset (Ren et al, 2021) showed that ZBP1 expression was significantly higher in COVID-19 patients in the progressive disease stage than those in the convalescent stage or healthy controls (Figure 7B). Monocytes and neutrophils have been found to be two major sources of cytokines in the peripheral blood that contribute to the "cytokine storm" in critically ill COVID-19 patients (Ren et al, 2021;Vanderbeke et al, 2021). Analysis of the single-cell RNAseq dataset (Ren et al, 2021) revealed an increase in ZBP1 expression in neutrophils and all major inflammatory subsets of monocytes in COVID-19 patients in progressive stage compared to convalescent stage patients (Figure S7A).…”
Section: Zbp1 Mediates Sars-cov-2-induced Cytokine Productionmentioning
confidence: 97%